2016
DOI: 10.1007/s10741-016-9544-9
|View full text |Cite
|
Sign up to set email alerts
|

A review on B-type natriuretic peptide monitoring: assays and biosensors

Abstract: Since its discovery in 1988, B-type natriuretic peptide (BNP) has been recognized as a powerful cardiovascular biomarker for a number of disease states, specifically heart failure. Concurrent with such a discovery, much effort has been allocated to the precise monitoring of physiological BNP levels. Thus, it can be used to guide the therapy of heart failure and determine the patient’s stage of disease. Thus, we discuss in this article BNP as a potent biomarker. Subsequently, we will review the progress of bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 125 publications
1
43
0
4
Order By: Relevance
“…B-type natriuretic peptide (BNP) has emerged as a powerful diagnostic tool for detecting acute HF and LV systolic and/or diastolic dysfunction. 8,9 In previous retrospective studies, a high BNP level was associated with left atrial appendage (LAA) thrombi, 10 and A trial fibrillation (AF) is the most common sustained arrhythmia. AF occurs together with many clinical risk factors and the development of AF is also influenced by genetic background.…”
mentioning
confidence: 99%
“…B-type natriuretic peptide (BNP) has emerged as a powerful diagnostic tool for detecting acute HF and LV systolic and/or diastolic dysfunction. 8,9 In previous retrospective studies, a high BNP level was associated with left atrial appendage (LAA) thrombi, 10 and A trial fibrillation (AF) is the most common sustained arrhythmia. AF occurs together with many clinical risk factors and the development of AF is also influenced by genetic background.…”
mentioning
confidence: 99%
“…BNP clearance is generally achieved by two routes, the most common one is binding to neutrophilic peptide chain endonuclease (NEP) on the membrane surface. In addition, BNP enters lysosomes through intracellular phagocytosis mediated by the receptor NPRC and then is degraded (27). Previous studies have suggested that BNP concentrations are strongly correlated with residual renal function (28,29), but several subsequent studies have reported that BNP only has a 21-22% or lower dependence on renal function for its clearance (30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…BNP is a well-known diagnostic and prognostic biomarker in congestive HF [ 182 ]. Over the past decades, several commercial measurement devices for BNP detection in HF were developed ( Table 2 ) [ 183 ]. In the literature, there are earlier studies that showed the measurement of BNP in three commercial assays: TRIAGE (fully automated immunoassay), IRMA (non-competitive immune-radiometric assay), and RIA (competitive immune-radiometric assay).…”
Section: Detection Of B-type Natriuretic Peptidesmentioning
confidence: 99%